Enhancing Basic Teaching Skills Through Guided Practice In Microteaching Learning - Kusmiarti, Reni; Bunga Wulandari, Ami; Paulina, Yanti; Zakaria, Jelita; Mahdijaya, Mahdijaya (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
Microteaching learning helps prospective teacher students hone their teaching skills before starting to work in real classrooms. Guided practice involves feedback and guidance from the supervising lecturer to support students' teaching practices. This research aims to describe the improvement of basic teaching skills through guided practice in microteaching learning. The method used is quantitative descriptive. The research subjects involve 13 students from the Indonesian Language and Literature Education Program. Data collection was conducted during microteaching sessions through direct observation by filling out instruments assessing basic teaching skill mastery. Data analysis techniques include several steps: (1) describing the data as a whole, (2) recording observation data in tables, (3) calculating values using the average and percentage formulas, (4) comparing the results with mastery level calculations, (5) interpretation and drawing conclusions. The research results conclude that the mastery level of basic teaching skills through guided practice in microteaching learning: the first teaching practice with an average score of 63.80 is at a good mastery level, the second teaching practice with an average score of 77.22 is at a good mastery level, and the third teaching practice with an average score of 84.77 is at a very good mastery level. The improvement in students' basic teaching skills through guided practice in microteaching learning from the first to the second teaching practice increased by 21.03%, the improvement from the second to the third teaching practice increased by 8.45%, and the overall improvement from the first to the third teaching practice increased by 31.26%."